Utilizing Modern Experimentation Method to Quantify Jet-Breaker Dimension Effects on Drop Manhole Pool Height - Seyedreza Hasheminejad; Mohammad-Javad Khanjani; Gholam-Abbas Barani (Salehan Institute of Higher Education, 2018)
Drop manholes are commonly employed in sewer and drainage systems to reduce pipes slope. The operation of these structures is dominated by their flow regime. Poor hydraulic performance of them under Regime R2 was improved with the jet-breaker, which intersects the inlet jet; yet its proper dimensions were needed to be precisely determined. In this paper, effects of jet-breaker length, width, sagitta, and angle on drop manhole pool free-surface height were experimentally studied under 80% filling ratio of the inlet pipe. The modern statistical Design of Experiment (DoE) methodology and dimensional analysis were utilized to design the experiments in accordance with the 24-1IV fractional factorial design. Consequently, nine specific jet-breakers were built and examined at two different angles, and under various flow rates. The statistical analysis of the results shown that manhole pool height was significantly decreased when jet-breaker length, width, and sagitta were 1, 1.4, and 0.7 times the inlet pipe diameter, respectively, and its angle was at 70°. The use of DoE resulted in 21% reduction in experimental runs, cost, and time, while it provided comprehensive data analysis and objective conclusion.